Direct momentum imaging of charge transfer following site-selective ionization - Allum, F; Kumagai, Y; Nagaya, K; Harries, J; Iwayama, H; Britton, M; Bucksbaum, PH; Burt, M; Brouard, M; Downes-Ward, B; Driver, T; Heathcote, D; et al. (American Physical Society, 2023)
We study ultrafast charge rearrangement in dissociating 2-iodopropane (2−C3H7I) using site-selective core ionization at the iodine atom. Clear signatures of electron transfer between the neutral propyl fragment and multiply charged iodine ions are observed in the recorded delay-dependent ion momentum distributions. The detected charge-transfer pathway is only favorable within a small (few angstroms), charge-state-dependent spatial window located at C-I distances longer than that of the neutral ground-state molecule. These results offer insights into the physics underpinning charge transfer in isolated molecules and pave the way for a different class of time-resolved studies.